Feasible Time for Extraction of Lead from Spent Paste by Pyrometallurgical Process - Ibraheem, Fakhri H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
This paper focuses on determining the feasible time for production of lead from spent paste (SP) by pyrometallurgical process through the rotary furnace. The extraction process faces several problems due to difficulties to control reaction media conditions. The experiments had been done on rotary furnace which exists in a secondary lead smelter in Baghdad - Khan Dhary. The SP mainly consists of lead sulfate and lead oxides. The experiments are implemented at high temperatures (1300°C) for reduction and desulfurization. 20 experiments were designed to determine the feasible smelting cycle time. The weight of slag, matte, and lead bullion was determined in each experiment as well as the percent of lead in each phase. These data were analyzed and graphically represented. The reaction’s rate profile can be detailed in the following manner: (1) High rate during the first 90 smelting min. Low rate from 90 to 120 min. Very low rate after 120 min. (2) The feasible extraction time is between 120 and 130 min with average lead percent in slag not >8%. (3) The slag with lead percent higher than 5% is returned to the furnace whereas the lower one is extracted by the blast furnace.